Analysis of Student Errors in Working Mathematical Problems in Calculated Operation Materials Fractions Based on Newman Stages From Adversity Quotient (Case Study in SMP Negeri 2 Sekampung) - Miiftakhul Fitri; Wardani Rahayu; Lukman El Hakim (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to find out the errors made by students and to find out the causes of student errors in doing arithmetic operations on fractions based on Newman's procedure in terms of Adversity Quotient. In this study, respondents were selected using purposive sampling. The research approach used is a descriptive qualitative approach, the method used is a case study. sampling The research subjects consisted of 3 students selected using a purposive technique. Data collection techniques used are documents, interviews, adversity quotient questionnaires, data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that errors occurred in every indicator of Newman's analysis. The types of errors that students make are reading questions, understanding problems, transforming, processing skills, and writing answers. The causes of these errors include limited students' reading comprehension abilities, students have not been able to identify relevant information in story problems, students are not used to working on story problems, poor time management, and students have not mastered mathematics, needed to solve operational problems properly.